Help your child learn to Read - Betty Root (USA Usborne Publishing, 1988)
This book shows what parents can do for a child from birth through preschool and early school years to help make the process of becoming a reader enjoyable and free of anxiety.
Keywords: Counsellor Resource -- Counsellor Resource